Patient selection algorithm for sellar remodeling in empty sella syndrome - Villalonga, Juan F.; Castillo, Andrea L.; Pailler, José Ignacio; Martinez-Font, Agustín; Campero, Álvaro (Revista Argentina de Neurocirugía, 2024)
Background: the extradural remodeling of the sellar floor is indicated in certain patients with primary empty sella syndrome; mainly when they have visual deficit without another cause that justifies it. Our team designed a preliminary algorithm for the selection of surgical patients. Objectives: to present the results of the application of this algorithm. Methods: from January 2020 to January 2024, this algorithm was applied prospectively to patients who presented empty sella syndrome during the medical consultation. Patients were categorized into three groups according to their visual field results: excellent (patients with improvement of visual deficit), acceptable (patients without progression of visual deficit) and poor (patients with progression of visual deficit). The minimum follow-up was 6 months. Results: regarding the visual outcome, 9 patients (69.2%) had an excellent result, while 3 patients (23.1%) had an acceptable result, and 1 patient (7.7%) had a poor result. Most patients (76.9%) had no complications. However, 1 patient (7.7%) suffered from panhypopituitarism, and 2 patients (15.4%) developed transient diabetes insipidus. Conclusion: the preliminary algorithm proved to be effective for the selection of patients with empty sella syndrome who are candidates for the surgical remodeling of the sellar floor.